DABCO dicationic ionic solid supported polymer (DDIS@PS) mediated synthesis of diverse 2-amino-4H-chromenes and xanthenes: a cascade Knoevenagel-Michael approach - Rajmane, Archana; Patil, Nita; Patil, Anuradha; Kamble, Sumit; Kumbhar, Arjun (New Journal of Chemistry, 2025)
This work documented the synthesis of diverse bioactive polysubstituted 2-amino-4H-chromenes using a DABCO dicationic ionic solid (DDIS) supported on Merrifield resin (DDIS@PS) as a catalyst. The catalyst is characterized by FT-IR, SEM-EDX, and TGA analysis. The resulting PS contains supported DABCO units with free tertiary nitrogen functionality on their external surface. The catalyst effectively catalyzed cascade Knoevenagel-Michael addition reactions of various aldehydes and active methylene compounds (malononitrile and phenyl sulfonyl acetonitrile) with dimedone, yielding good to excellent results in water or ethanol at room temperature or 78 degrees C. The time required for the reaction of phenyl sulfonyl malononitrile is comparatively very high compared to malononitrile. The synthesis of bis-dimedone derivatives and 1,8-dioxo-octahydro-xanthenes was also achieved in both solvents at RT and 78 degrees C, with high yields. The catalyst demonstrated greater efficiency and maintained its activity over at least five cycles.